Biomechanical and psychosocial exposures are independent risk factors for carpal tunnel syndrome: assessment of confounding using causal diagrams. Issue 11 (27th July 2016) - Harris-Adamson, Carisa; Eisen, Ellen A; Neophytou, Andreas; Kapellusch, Jay; Garg, Arun; Hegmann, Kurt T; Thiese, Matthew S; Dale, Ann Marie; Evanoff, Bradley; Bao, Stephen; Silverstein, Barbara; Gerr, Fred; et al.
Abstract : Background: Between 2001 and 2010, six research groups conducted coordinated prospective studies of carpal tunnel syndrome (CTS) incidence among US workers from various industries to estimate exposure–response relationships. Objective: This analysis examined the presence and magnitude of confounding between biomechanical and workplace psychosocial factors and incidence of dominant-hand CTS. Methods: 1605 participants, without CTS at enrolment, were followed for up to 3.5 years (2471 person-years). Demographic information, medical history and workplace psychosocial stress measures were collected at baseline. Individual workplace biomechanical exposures were collected for each task and combined across the workweek using time-weighted averaging (TWA). CTS case criteria were based on symptoms and results of electrophysiological testing. HRs were estimated with Cox proportional hazard models. Confounding was assessed using causal diagrams and an empirical criterion of 10% or greater change in effect estimate magnitude. Results: There were 109 incident CTS cases (IR=4.41/100 person-years; 6.7% cumulative incidence). The relationships between CTS and forceful repetition rate, % time forceful hand exertion and the Threshold Limit Value for Hand Activity Level (TLV-HAL) were slightly confounded by decision latitude with effect estimates being attenuated towards the null (10–14% change) after adjustment. The risk of CTS among participants reporting high job strain was attenuated towards the null by 14% after adjusting for the HAL Scale or the % time forceful hand exertions. Conclusions: Although attenuation of the relationships between CTS and some biomechanical and work psychosocial exposures was observed after adjusting for confounding, the magnitudes were small and confirmed biomechanical and work psychosocial exposures as independent risk factors for incident CTS.